RECYCLE GLASS WASTE AS A REPLACEMENT OF FINE AGGREGATE IN CONCRETE MIX STANDARD COMPARISON - Syf. Umi Kalsum; Polonia, Betti Ses Eka; Hurul 'Ain (Jurnal Teknik Sipil, 2021)
Recycling is one way that is used to minimize the amount of waste that exists. Recycling is also a process to reduce the use of new raw materials, reduce energy use, reduce pollution, land degradation and greenhouse gas emissions. Materials that can be recycled consist of waste of glass, plastic, paper, metal, textiles and electronic goods. Glass has characteristics suitable as concrete aggregates, considering that glass is a material that does not absorb water. In addition, glass has high abrasion resistance. Meanwhile, the waste glass flux lowers the temperature to the temperature at which the formers will melt. Stabilizers in glass waste are made of calcium carbonate, which makes the glass waste solid and water-resistant. This glass waste is recycled by mixing it into the concrete mix. The recycling method is done by pounding the glass and putting it into the concrete mix stage. The purpose of mixing the glass waste is expected to increase the compressive strength of concrete. The use of glass waste as a mixed material affects the compressive strength of the concrete. The concrete with the most inferior to highest compressive strength is 4% variation concrete, 2% variation concrete, and traditional concrete. Optimal percentage addition of glass waste impacts on maximum concrete compressive strength is 2% mixture variation which obtained 11,88 Mpa & 11,32 Mpa.